Mechanosensor YAP mediates bone remodeling via NF-κB p65 induced osteoclastogenesis during orthodontic tooth movement - Jie Deng; Yu-Ning Zhang; Ru-Shui Bai; Ting-Ting Yu; Yi Zhao; Hao Liu; Yun-Fan Zhang; Tian-Min Xu; Bing Han (Progress in Orthodontics)
Abstract Background Yes-associated protein (YAP) is a crucial mechanosensor involved in mechanotransduction, but its role in regulating mechanical force-induced bone remodeling during orthodontic tooth movement (OTM) is unclear. This study aims to elucidate the relationship between mechanotransduction and mechanical force-induced alveolar bone remodeling during OTM. Results Our study confirms an asynchronous (temporal and spatial sequence) remodeling pattern of the alveolar bone under mechanical force during OTM. Both compression and tension activate osteoclasts recruiting to the alveolar bone, whereas no significant presence of osteoblasts in the alveolar bone at the early stages of bone remodeling. Specifically, applying different force magnitudes (10, 25, 50, 100 g) to rats’ 1st molars affected OTM distance. Force-induced alveolar bone remodeling was characterized by osteoclastogenesis and YAP activation at compressive/tensile sites on day 1 of OTM. Notably, 25 g force triggered peak YAP expression and osteoclastic activity early on. Time-course analysis revealed two YAP activity peaks on day1 and 14, contrasting with one peak of type I collagen expression on day14. In addition, RNA-sequencing highlighted increased nuclear factor kappa B (NF-κB) signaling, mineral absorption, and osteoclast differentiation at day-1 and 3. Moreover, gene expression analysis showed similar trends for NF-κB p65, YAP1, and TEA domain 1 (TEAD1) during this time. Furthermore, experiments on osteoclast cultures indicated YAP activation via large tumor suppressor (LATS) and TEAD under mechanical stimuli (compression/tension), promoting osteoclastogenesis by regulating NF-κB p65 and receptor activator of NF-κB (RANK). Inhibiting YAP with verteporfin delayed OTM by impairing force-induced osteoclastic activities in vivo and ex-vivo. Conclusions We propose that YAP mediates alveolar bone remodeling through NF-κB p65-induced osteoclastogenesis in an asynchronous remodeling pattern during OTM. Both compression and tension activate osteoclasts recruiting to the alveolar bone at early stages of bone remodeling, offering evidence for orthodontists as a reference.